2023
DOI: 10.18485/aeletters.2023.8.1.5
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Multi-Body Modeling and Vibration Analysis for Twin-Barrel Gun While Firing on Elastic Ground

Abstract: In this paper, we propose a new twin-barrel gun model for calculating firing on the elastic ground to study the effects of structural parameters on the weapon's performance. This paper intends to provide a theoretical basis and establish a specific model of twin-barrel gun, to build a system of differential equations of vibration, and to determine the rules of vibration of the gun when firing on the elastic ground. The method is used to establish a model of two sets of automatic firing systems by dynamics of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Research [9][10][11] has shown the influence of losses occurring in the gas chamber such as heat loss, flow constriction loss, or friction loss. In addition, the influence of the position of the gas block hole, the diameter of the gas block hole, and the initial volume of the gas chamber are also presented in the literature [12][13][14][15][16]. However, there have been no studies that have built a model to study the relationship between the gas block hole crosssection and the gas exhaust hole cross-section.…”
Section: Introductionmentioning
confidence: 99%
“…Research [9][10][11] has shown the influence of losses occurring in the gas chamber such as heat loss, flow constriction loss, or friction loss. In addition, the influence of the position of the gas block hole, the diameter of the gas block hole, and the initial volume of the gas chamber are also presented in the literature [12][13][14][15][16]. However, there have been no studies that have built a model to study the relationship between the gas block hole crosssection and the gas exhaust hole cross-section.…”
Section: Introductionmentioning
confidence: 99%
“…For weapons, the muzzle device is considered an important component in the weapon system, it is diverse, with many types with different uses such as muzzle brakes, flash hiders, muzzle deflectors, recoil intensifiers, silencers, etc. At the same time, some muzzle devices affect the gun's stability during firing [2][3][4].…”
Section: Introductionmentioning
confidence: 99%